Peran Kerjasama Tim dan Kefektivitasan Komunikasi Interpersonal Kinerja Divisi Transaction Processing pada PT. Bank Tabungan Negara (Persero) Tbk Kc. Medan - Ananda, Fitri Tia; Rahmadhani, Sri (Jurnal Manajemen Akuntansi (JUMSI), 2022)
In a world of work that involves many people, of course the role of teamwork is needed. This also applies to the performance procedures at PT. Bank Tabungan Negara (Persero) tbk KC Medan, in which there are many work divisions, so it must create teamwork that builds each other. Teamwork can be started with strategies that are formed through good communication between employees. communication that is formed is not only formal, but sometimes interpersonal communication is very effective to play. A relaxed demeanor but still in a serious condition in interpersonal communication, making it easier for employees to be able to improve teamwork. From the strategies carried out by employees, they can find out the process without obstacles and also advance the activity system in the Transaction Processing Division in processing and entering data in an orderly and neat manner. This level of performance will be a feedback process on previous performance, can improve employee performance in the future.